European survey on CAR T-Cell analytical methods from apheresis to post-infusion immunomonitoring - De Angelis, Biagio; D’Amore, Maria Luisa; Lecot, Pacôme; Neininger, Kerstin; Lorrain, Margot; Gambotti, Laetitia; Dreuillet, Caroline; Courcault, Elise; Chatterjee, Sampurna; Delgado, Julio; Galy, Anne; Franz, Paul; et al. (Frontiers in Immunology, 2025)
BackgroundChimeric Antigen Receptor (CAR) T-cell therapy has emerged as a revolutionary approach to cancer treatment. Given the rapid expansion of new indications addressed by newly developed CAR T-cell products, it is essential to standardize analytical methods for the characterization/monitoring of apheresis materials, drug products, and post-infusion patient samples.MethodsThe T2Evolve Consortium, part of the European Union's Innovative Medicines Initiative (IMI), conducted an extensive anonymous online survey between February and June 2022. Comprising 36 questions, the survey targeted a wide range of stakeholders involved in engineered T-cell therapies, including researchers, manufacturers, and clinicians. Its goal was to address the current variability within the CAR T-cell field, focusing on analytical assays for quality control of apheresis materials, drug products, and post-infusion immunomonitoring. Another objective was to identify gaps and needs in the field.ResultsA total of 53 respondents from 13 european countries completed the survey, providing insights into the most commonly used assays for apheresis material and drug product characterization, alongside safety and efficacy tests required by the Pharmacopeia. Notably, a minority of respondents conducted phenotypical characterization of T-cell subsets in the drug product and assessed activation/exhaustion T cell profiles.ConclusionThe survey underscored the necessity to standardize CAR T-cell functional potency assays and identify predictive biomarkers for response, relapse, and toxicity. Additionally, responses indicated significant variability in CAR T-cell monitoring during short-term patient follow-up across clinical centers. This European survey represents the first initiative to report current approaches in different stages of CAR T-cell therapies via a survey, from drug product quality controls to post-infusion immunomonitoring. Based on these findings, and with input from T2EVOLVE experts, the next step will be to address harmonization in the identified areas. These efforts are anticipated to significantly enhance cancer patients' access to engineered T cell therapy safely and effectively throughout Europe.